FRI0154 The Spondyloarthritis Research Consortium of Canada MRI Sacroiliac Joint Structural Score: Reliable Detection of Structural Progression Even over One Year. (10th June 2014) - Maksymowych, W.P.; Wichuk, S.; Chiowchanwisawakit, P.; Lambert, R.G.; Pedersen, S.J.
Abstract : Background: With increasing focus on effective treatment intervention in early spondyloarthritis (SpA), there is an unmet need for reliable assessment of structural progression in the sacroiliac joints (SIJ) but radiography is unreliable for detecting change and lacks responsiveness. There has been limited validation of MRI-based scores for structural lesions in the SIJ but it is unclear whether change in structural progression can be reliably detected, especially over a time frame shorter than 2 years. Objectives: To assess the reliability of a new MRI-based scoring method for detecting change in structural damage in the sacroiliac joints of patients with SpA. Methods: The SPARCC SIJ Structural Score (SSS) method for assessment of structural lesions on T1WSE MRI scans is based on: 1. Validated definitions of structural lesions, 2. Anatomical matching of all time points according to the transitional SIJ slice, defined as the first slice in the cartilaginous portion that has a visible portion of the ligamentous joint, 3. Dichotomous scoring (present/absent) of lesions in SIJ quadrants (fat, erosion) or halves (backfill, ankylosis), 4. Assessment of 5 consecutive slices from the transitional slice anteriorly through the cartilaginous portion of the joint. Scoring ranges are: fat metaplasia (0-40), erosion (0-40), backfill (0-20), ankylosis (0-20). We progressively conducted 3 validation exercises with 2-4 readers according to the Outcome Measures in Rheumatology (OMERACT) filter on baseline and either 2-year (exercises 1 and 2) or 1 year (exercise 3) scans from 147 patients with SpA assessed blinded to time point. Inter-observer reliability was assessed by intra-class correlation coefficient (ICC3, 1). The smallest detectable change (SDC) was calculated using the Bland-Altman 80% levels of agreement. Results: Change >0 in SSS score in patients after one year of follow up was recorded in 51 to 69% for fat metaplasia, 60 to 90% for erosion, 48 to 85% for backfill, and 35 to 53% for ankylosis for the 3 exercises. Mean change scores were 0.21 to 0.73, -0.63 to -1.32, -0.03 to 0.5, and 0.15 to 0.58 for fat, erosion, backfill and ankylosis, respectively. The SDC was comparable for structural lesion scores at 5-7% of the scoring range with the exception of backfill (14%). For status scores, excellent reliability was observed for ankylosis and good reliability for fat metaplasia and erosion. For change scores at 1 and 2 years, fair reliability was observed for all SSS scores despite the small degree of change. Conclusions: The SPARCC MRI SSS method is a reliable scoring method for detecting structural progression in the sacroiliac joints, especially ankylosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3755